2020
DOI: 10.1111/jmwh.13122
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of Gestational Diabetes Provide a Lens to Tailor Postpartum Prevention and Monitoring Counseling

Abstract: Introduction: Women with gestational diabetes mellitus (GDM) have a marked increased risk of early onset type 2 diabetes, but less than half initiate postpartum glucose testing or connect with a primary care provider for continued follow-up after giving birth. This study analyzed women's narratives about their GDM-affected pregnancies to (1) identify different patterns (narrative archetypes) that capture the GDM experience; (2) explore how these patterns relate to awareness of ongoing risk after pregnancy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…While awareness of the need for screening was typically high, lack of awareness of a link between gestational diabetes and future type 2 diabetes risk was a key barrier. Many studies highlighted women's perceptions of gestational diabetes as ‘an acute phenomenon…confined to pregnancy’, 49 prompting one author to recommend that ‘interventions are needed to raise postpartum diabetes risk awareness’ 54 . Relatedly, women reported confusion about the risk of conversion to type 2 diabetes: ‘You've got the glucose intolerance test, but I don't know how far after that people would develop diabetes’ 55 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While awareness of the need for screening was typically high, lack of awareness of a link between gestational diabetes and future type 2 diabetes risk was a key barrier. Many studies highlighted women's perceptions of gestational diabetes as ‘an acute phenomenon…confined to pregnancy’, 49 prompting one author to recommend that ‘interventions are needed to raise postpartum diabetes risk awareness’ 54 . Relatedly, women reported confusion about the risk of conversion to type 2 diabetes: ‘You've got the glucose intolerance test, but I don't know how far after that people would develop diabetes’ 55 .…”
Section: Resultsmentioning
confidence: 99%
“…In three cases, more than one paper described the same study and reported different outcomes. For each instance, we nominated the study as the unit of interest 43 and the earliest publication as the primary source 44–46 retaining the secondary papers 47–50 …”
Section: Resultsmentioning
confidence: 99%
“…We nominated the study as the unit of interest, 59 the earliest publication 60 , 61 , 62 as the primary source and retained the secondary papers. 63 , 64 , 65 …”
Section: Resultsmentioning
confidence: 99%
“…Some women believed GDM was ‘confined to pregnancy’ and were unaware of future risks. 60 , 62 , 63 , 65 , 77 For them, risk beyond the immediate postpartum period was not a concern. 60 , 63 , 77 Thus, ‘many reverted to previous diet habits … and did not engage in … prevention activities’.…”
Section: Resultsmentioning
confidence: 99%
“…Although GDM pharmacotherapy generally can be stopped after delivery, the American Diabetes Association recommends regular glucose monitoring starting a few days after delivery, at 2–6 months postpartum and every 1–3 years thereafter [ 42 ]. Open-ended interviews conducted with women with GDM revealed that many women considered GDM as an acute, resolvable condition that does not require further surveillance and worry and only a small minority considered it a wake-up call for continuing healthy lifestyle [ 43 ]. Understanding this narrative can help clinicians better communicate with affected women to improve transition in care after delivery.…”
Section: Addressing Maternal Cardiovascular Risk Profile In the Fourt...mentioning
confidence: 99%